Menerapkan metode pembelajaran kuis interaktif berbasis Mentimeter pada mata pelajaran Pendidikan Agama Islam - Mailani, Leni (Maliki Interdisciplinary Journal, 2024)
This study intends to find out whether the application of a meter-based interactive quiz learning approach to Islamic Religious Education (PAI) subjects results in an increase in student learning outcomes. Classroom Action Research (CAR) is the research methodology used. The sample for this research consisted of 21 fifth grade students at SD Muhammadiyah 1 Malang. This research uses one pre-cycle stage and two cycle stages with various actions in its implementation. The first two cycles used a meter-based interactive quiz learning approach with several treatments, while the pre-cycle was carried out using the lecture learning method. Each cycle will be assessed by quizzes to find out whether the meter-based interactive quiz learning approach has improved student learning outcomes. The average student score in the pre-cycle was 45.7 and only 14.3% of students completed the KKM. The student pass percentage was 38.1%, while student learning outcomes in the first cycle assessment were 72.4. With a graduation rate of 100% and an average student score in the previous cycle of 91.4, all students met the KKM of 75.